Multiplex precise base editing in cynomolgus monkeys - Wenhui Zhang (Nature Portfolio, 2020)
Due to the polygenic nature of most diseases, simultaneous correction or introduction of single nucleotide variants is needed. Here, the authors demonstrated the feasibility of multiplex base editing for polygenes disease modeling in cynomolgus monkey embryos with high specificity.